Verrucous Carcinoma of Gingiva - Chanau, Ram Prakash Roy; Sharma, Shivalal; Goel, Khushboo; Shrestha, Sajeev; Acharya, Pujan; Shrestha, Ashish (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
hghghg